2013
DOI: 10.1111/zoj.12056
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy, biogeography and DNA barcodes ofGeodiaspecies (Porifera, Demospongiae, Tetractinellida) in the Atlantic boreo-arctic region

Abstract: Geodia species north of 60°N in the Atlantic appeared in the literature for the first time when Bowerbank described Geodia barretti and G. macandrewii in 1858 from western Norway. Since then, a number of species have been based on material from various parts of the region: G. simplex, Isops phlegraei, I. pallida, I. sphaeroides, Synops pyriformis, G. parva, G. normani, G. atlantica, Sidonops mesotriaena (now called G. hentscheli), and G. simplicissima. In addition to these 12 nominal species, four species desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 82 publications
10
100
0
Order By: Relevance
“…Sponge aggregations dominated by the same set of species have been described also from the Icelandic shelf, the Reykjanes Ridge, the Faroe Island shelf, west of the Shetland Islands and off Newfoundland (Bett, 2001;Klitgaard and Tendal, 2004;Murillo et al, 2012;Cárdenas et al, 2013). This specific type of sponge habitat is generally referred to as ostur communities (Hogg et al 2010) and have been defined by Klitgaard and Tendal (2001) as a restricted area where large sponges are strikingly common and where sponges are estimated to constitute more than 90% of the biomass, excluding benthic fish, in a trawl haul.…”
Section: Introductionmentioning
confidence: 65%
“…Sponge aggregations dominated by the same set of species have been described also from the Icelandic shelf, the Reykjanes Ridge, the Faroe Island shelf, west of the Shetland Islands and off Newfoundland (Bett, 2001;Klitgaard and Tendal, 2004;Murillo et al, 2012;Cárdenas et al, 2013). This specific type of sponge habitat is generally referred to as ostur communities (Hogg et al 2010) and have been defined by Klitgaard and Tendal (2001) as a restricted area where large sponges are strikingly common and where sponges are estimated to constitute more than 90% of the biomass, excluding benthic fish, in a trawl haul.…”
Section: Introductionmentioning
confidence: 65%
“…In the northwest Atlantic, the upper depth limit of sponge grounds dominated by astrophorid sponges (referred to as 'ostur' in the northeast Atlantic; Klitgaard et al, 1997;Klitgaard and Tendal, 2004) typically occur at depths 4800 m (Fuller, 2011;Murillo et al, 2012;Beazley et al, 2013;Knudby et al, 2013b) as observed in this study. In the northeast Atlantic ostur have a broader depth range (Bett and Rice, 1992), having been reported as shallow as 180 m (Klitgaard et al, 1997) with individual Geodia species found in less than 100 m of water (Cárdenas et al, 2013;van Soest, 2014).…”
Section: Megafaunal Community Patterns On the Sackville Spurmentioning
confidence: 99%
“…Of the taxa eliciting a large response at 15 sponges m À 2 , the yellow encrusting sponge Hexadella dedritifera showed the most rapid change in abundance. This species is fairly common in ostur communities in the northeast Atlantic, where it occurs as an epibiont of Geodia phlegraei, G. parva, and other astrophorids such as Stryphnus fortis and Stelletta normani (Cárdenas et al, 2013). On the Sackville Spur H. dedritifera was observed encrusting primarily on unidentified sediment-covered astrophorids, and was not found on Geodia cf.…”
Section: Drivers Of Megafaunal Composition In the Sponge Grounds Of Tmentioning
confidence: 99%
“…The genus Stryphnus dominates on the northern shelf edge of the Faroes (Hogg et al 2010), whereas extensive sponge grounds dominated by Geodia sp. are found elsewhere around the Faroes (Klitgaard and Tendal 2004;Cárdenas et al 2013) and in the north-west Atlantic (Knudby et al 2013). Dense aggregations of the glass sponge Pheronema carpenteri occur on the Porcupine Sea Bight southwest of Ireland (Rice et al 1990) and further south off the Iberian Peninsula and the Moroccan coast (Reiswig and Champagne, 1995;Barethel and Thiel 1996).…”
Section: Introductionmentioning
confidence: 99%